2019
DOI: 10.1088/1361-6552/aaf95d
|View full text |Cite
|
Sign up to set email alerts
|

Engaging physics teacher-candidates in the production of science demonstration videos

Abstract: This paper describes how future physics teachers' involvement in annual Family Math and Science Day-a public outreach event at the University of British Columbia, Canada-has a potential to transform them as physics demonstration experts and amateur video producers. These science demonstration videos serve as teaching and learning resources not only for their own coursework, practicum, and postgraduation, but also as a useful resource for their peers and other educators. The production of demonstration videos w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The preliminary results of this analysis indicate that teacher-candidates' active engagement with technology as students in their methods courses has a significant impact on their growth mind set and positive attitude about student STEM engagement (Milner-Bolotin & Milner, 2017;Tembrevilla & Milner-Bolotin, 2019). These data will provide information for the consequent implementation of research-based STEM methods courses in the fall of 2019.…”
Section: Structurementioning
confidence: 88%
See 1 more Smart Citation
“…The preliminary results of this analysis indicate that teacher-candidates' active engagement with technology as students in their methods courses has a significant impact on their growth mind set and positive attitude about student STEM engagement (Milner-Bolotin & Milner, 2017;Tembrevilla & Milner-Bolotin, 2019). These data will provide information for the consequent implementation of research-based STEM methods courses in the fall of 2019.…”
Section: Structurementioning
confidence: 88%
“…Second stage. The learning environments suggested in the first stage were piloted in the STEM methods courses in the fall of 2017 (Milner-Bolotin, 2017;Tembrevilla & Milner-Bolotin, 2019). The data on the implementation was collected and is currently being analyzed.…”
Section: Structurementioning
confidence: 99%
“…While the study is still ongoing, the feedback from FPT at UBC collected through anonymous end of course student evaluations indicated that the process of designing the videos helped them to feel more confident in being able to engage students in hands-on science, to design experiments on a shoe-string budget [2]. The FPTs were especially proud to share their work online with other STEM educators.…”
Section: Impact Of the Video Design Assignment On Ubc Fptsmentioning
confidence: 99%
“…We examine a pedagogical intervention that uses science video making to improve future physics teachers' (FPTs') experimental, pedagogical, and content knowledge [1] while creating a collection of research-based pedagogical resources to be used during the school practicum or consequent teaching. The effects of different pedagogical approaches that incorporated these videos on secondary students' learning were also investigated [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation